(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Drones are used in daily life for security purpose, farming, video shooting and product delivery. drones are working on the principal of The Newton’s Third law of motion that is also known as action and reaction. Mostly used in Aerial photography for films express shipping, gathering information, Geographic mapping of the location. Drones are also used for patrolling by the government police they are monitoring the particular areas by the drone camera for this work there is a need of skilled drone driver for flying and monitoring. We present a model of drone which is Automatically flying around particular areas in fixed timing and automatically detect the objects, Animals, humans and their Activity and it will detect fire, violence. If any criminal activities are detected by the drone then it is directly reported to the end device. In this model we used the satellite communication for the controlling drone and information transmission, Internet of things and machine learning & computer Vision model for crime detection.